Dampak Poligami Tanpa Ijin Pengadilan Terhadap Hak Keperdataan Istri (Studi Putusan Pengadilan Tinggi Agama Samarinda Nomor 28/Pdt.G/2021/PTA.Smd) - Syahria; Moh. Mahrus; Muhammad Yusuf Qardlawi (Bulletin of Community Engagement, 2024)
The state through the law has regulated how someone who wants to practice polygamy so that all parties get legal protection. Especially legal protection for wives and children. However, in fact, there are still many who practice polygamy without getting permission from the religious court. Various methods are used to be able to practice polygamy without court permission which is then often referred to as wild polygamy. The main reason is that the husband does not want the first wife to know about his polygamy practice because the first wife did not give permission and could still fulfill her obligations as a wife. The community also still considers that polygamy permission from the religious court is only an additional rule that does not interfere with the validity of polygamous marriages and is not a teaching of Islamic law. The reasons above are what make the practice of wild polygamy still rife in Indonesia. One example and used as research material in this journal is the decision of the Samarinda High Religious Court number 28/Pdt.G/2021/PTA.Smd. The decision explains the application for annulment of the second marriage of a husband (NS) with his second wife (A) which was filed by the first wife (PR) because the second marriage was without permission for polygamy. The results of the court's decision stated that the Panel of Judges did not annul the marriage between NS and A, however A did not have a civil relationship in the form of zaujiyah maintenance, joint property and inheritance in accordance with the Circular of the Supreme Court Number 2 of 2019 Number 1 letter (f).